Minimal Enzymes Cocktail Development by Filamentous Fungi Consortia in Solid-State Cultivation and Valorization of Pineapple Crown Waste by Enzymatic Saccharification - Teixeira, Wéllen Fabrícia Aviz; Batista, Ryhára Dias; do Amaral Santos, Claudia Cristina Auler; Júnior, Aloísio Chagas Freitas; Terrasan, César Rafael Fanchini; de Santana, Marcio Waluce Pinheiro R.; de Siqueira, Félix Gonçalves; de Paula-Elias, Fabrício Coutinho; de Almeida, Alex Fernando (Springer Nature, 2021)
Agroindustrial wastes is an interesting opportunity for enzymes production, reducing operational costs and strengthening the biorefineries concept. The conversion of lignocellulosic waste to fermentable sugars is current challenge for biorefineries industries. Enzyme cocktail used in delignification and saccharification platform are produced by a combinatory of several lignocellulolytic enzymes. The aim of this study was to develop filamentous fungi compatible-consortia isolated from pineapple wastes for cellulose-degrading enzymes production using pineapple crown waste in solid-state cultivation and its potential for saccharification of pineapple crown waste. Isolates were screened in agar-plate and in solid-state cultivation for cellulases, xylanase and pectinases productions. Six compatible consortia of Trichoderma strains with Aspergillus niger or Pleurotus ostreatus were evaluated for SSC using pineapple crown. All consortia increased the enzymes production compared to monoculture. Consortia of Trichoderma asperellum PEC-6 and P. ostreatus increased 1.60-fold the xylanase and 1.42-fold the β-glucosidase productions. T. asperellum PEC-17 and A. niger increased 1.16-fold endoglucanase and 1.28-fold pectinase. Saccharification of pineapple crown waste using enzyme cocktail produced by filamentous fungi consortia increased the total reducing sugar released in 12.50–13.93% compared to enzymes produced by monocultures. This study provides an alternative model to the cocktail enzyme production by mixed cultures development with lower cost of on-site enzyme manufacture by use of agroindustrial wastes eliminating an enzyme blended step. Moreover, the procedure used in this work can be potentially cost saving and environmentally friendly and should be explored on other bioenergy feedstocks and feed production. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: biomass saccharification; Enzyme production; Microbial consortia; Solid-state cultivation; Trichoderma